Improving The Reading Comprehension of The Eight Grade Students of SMP Negeri 12 Parepare Through Guessing Game - Soraya, Ayu (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2018)
Reading comprehension is one of English aspect that is not easy to be learned. When doing observation at SMP Negeri 12 Parepare, the researcher found that the students’ reading comprehension was low. It was caused by the unsatisfied of the teacher’s technique in teaching learning process. The researcher has suggested a technique namely guessing game to solve the problems. Then, the objective of this research is to find out whether or not the use of guessing game able to improve the students' reading comprehension. The researcher applied quasi-experimental method, with two group pre- test and post- test design. The samples in this research consisted of 40 students from two classes. The first is experimental class handled through guessing game and the second is control class handled through think pair share. It is taken from the population of the eight grade students of SMP Negeri 12 Parepare. The researcher used cluster random sampling technique. The result of the data analysis shows that the students’ reading comprehension improved significantly. It was showed that the mean score of pre-test was 46.66 and post-test was 72.33. It proves that the use of contextual guessing technique can improve the reading comprehension of the eight grade students of SMP Negeri 12 Parepare. After analyzing the data by using SPSS ver. 21.0, the result of t-test value was 2.394. In this case, t-test value was (2394) was higher than t-teble value (2040). It means that H0 is rejected and H1 is accepted.